ESK Pengaruh Penerapan Konsep Matematika Gasing dalam Meningkatkan Kemampuan Penjumlahan Bilangan Bulat Guru SDIT Auladi Plaju - Endang Sri Kresnawati; Novi Rustiana Dewi; Bambang Suprihatin; Yulia Resti (Universitas Mathla'ul Anwar Banten, 2021)
THE EFFECT OF MATEMATIKA GASING CONCEPTS APPLICATION IN IMPROVING THE ADDITION SKILL OF SDIT AULADI PLAJU TEACHERS. The teacher is the spearhead of the mathematics learning process at the elementary school level (SD). The SD curriculum applies a thematic system, where lower-level classes, grades 1, 2, and 3 are guided by a class teacher who is responsible for delivering material for all subjects. Includes math subjects. Problems arise when the teacher does not master the material, mathematical concepts. This is due to the background of most classroom teachers not from the field of mathematics. One of the approaches used to help increase teachers' knowledge is Gasing mathematics. In accordance with the level, the mathematical concept conveyed in the training is addition. The activity method is a general lecture and demonstration using simple props and items in the school environment. The evaluation results showed an increase in the participants' abilities by 55% compared to before. This means that the top method has succeeded in increasing the teacher's ability to complete additions more quickly and correctly.